Dogs and Disease Threats to Giant Pandas in China. Issue 2 (19th November 2019) - Yan, Xia; Owens, Jacob R.; Wen, Yiping; Su, Xiaoyan; Wang, Zhenghao; Liu, Songrui; Zhang, Dongsheng; Callan, Ramana; Wenlei, Bi; Qi, Dunwu; Spotila, James R.; Hou, Rong; et al.
Abstract : Numerous free‐ranging domestic dogs were located close to Liziping National Nature Reserve, a primary location of giant panda reintroductions and conservation. Viral and parasitic disease threats to giant pandas and other wildlife were present in the population, indicating a need for immediate management action. ABSTRACT: The potential threat of domestic dogs to wildlife habitat in China is not widely recognized, despite their large population, lack of regulations regarding their control, and threat they pose to native species. In a case study in 2017, we surveyed villages surrounding Liziping Nature Reserve, the primary site for the release of captive‐born giant pandas ( Ailuropoda melanoleuca ) into the wild. We conducted surveys of dog owners to assess the population size, demographics, free‐roaming status, and vaccination and sterilization history of their dogs. We collected blood and fecal samples to assess the prevalence of viral and parasite disease threats. At least 370 owned dogs lived near the core giant panda habitat; 64% were free‐roaming, 21% had positive antibody titers for ≥1 of the 4 viruses we tested (canine distemper, parvovirus, rotavirus, rabies), and 67% were positive for gastrointestinal parasites. The high proportion of free‐roaming dogs, uninhibited access to the reserve, and high prevalence of infectious diseases indicate that dogs pose a serious threat to wildlife within Liziping. The extent of this threat throughout the giant panda nature reserve network is unknown and should be assessed. © 2019 The Authors. Journal of Wildlife Management published by Wiley Periodicals, Inc. on behalf of The Wildlife Society.